Pain management in bleeding disorders care: perspectives of Canadian Social Workers in Hemophilia Care - King Jennifer; Fletcher Kara; Tupper Susan M.; Brose Kelsey; Goodridge Donna (The Journal of Haemophilia Practice, 2020)
Pain associated with bleeding disorders has been demonstrated to have an impact on patients’ and families’ quality of life. Both acute and chronic pain are common experiences and require attention by professionals working in haemophilia treatment centres (HTCs). The benefits of psychological pain management strategies such as cognitive behaviour therapy and self-management skills training are well documented; however, it is not well understood how Canadian social workers involved in haemophilia care perceive and provide pain management support to patients.